A Critical Study of Adolescent Social Interactions from Ibn Miskawaih's Perspective - Imam Fadaah; Irwan Supriadin; Junaidin Junaidin (Fitrah, 2025)
This study aims to analyze the social life of adolescents in Bima from the perspective of Ibn Miskawaih and its relevance to the concept of Maja Labo Dahu . With the increase in negative behavior among adolescents, such as delinquency, fighting, and drug abuse, this study focuses on how moral values can be applied to improve the social life of adolescents in Bima. This study uses Literature Study research based on the Indonesian translation of the work by Hidayat Helmi " philosophy of morals, first principles, towards moral perfection". To strengthen this research, the researcher uses content analysis from various sources, including books, journals, and relevant articles. After conducting the research, the researcher produces that the social life of adolescents in Bima can be improved through the application of moral values taught by Ibn Miskawaih, which emphasizes the control of reason, lust, and anger, as well as the concept of Maja Labo Dahu which teaches shame and fear of mistakes. These two concepts complement each other in forming good adolescent character. This study concludes that continuous moral education in the family, school, and community environments is very important to shape positive adolescent behavior. Thus, the application of the values of these two concepts is expected to direct adolescent social interactions in a better and more responsible direction.